2018
DOI: 10.3389/fimmu.2018.00484
|View full text |Cite
|
Sign up to set email alerts
|

Immune Control of Burkholderia pseudomallei––Common, High-Frequency T-Cell Responses to a Broad Repertoire of Immunoprevalent Epitopes

Abstract: Burkholderia pseudomallei (Bp) is an environmental bacterial pathogen that causes potentially lethal sepsis in susceptible individuals and is considered a Category B, Tier-1 biothreat agent. As such, it is crucial to gain an improved understanding of protective immunity and potential vaccine candidates. The nature of immune correlates dictating why most exposed individuals in endemic regions undergo asymptomatic seroconversion while others succumb to life-threatening sepsis is largely uncharted. Bp seroreactiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 56 publications
(68 reference statements)
0
17
0
Order By: Relevance
“…Cell-mediated immune responses by IFN-γ and type I immune responses (e.g., interleukin [IL] 12, IL-18, tumor necrosis factor α) are essential for the host immune system in fighting against intracellular infections (29)(30)(31). Nithichanon et al showed that most of an exposed healthy population has acquired cellular immunity against broad immunogenic B. pseudomallei epitopes (32). Our IFN-γ ELISpot experiments suggest that both melioidosis patients and HH contacts engage strong cross-immune IFN-γ responses between B. pseudomallei, B. thailandensis, and BTCV, despite low humoral responses in the HH cohort.…”
Section: Discussionmentioning
confidence: 99%
“…Cell-mediated immune responses by IFN-γ and type I immune responses (e.g., interleukin [IL] 12, IL-18, tumor necrosis factor α) are essential for the host immune system in fighting against intracellular infections (29)(30)(31). Nithichanon et al showed that most of an exposed healthy population has acquired cellular immunity against broad immunogenic B. pseudomallei epitopes (32). Our IFN-γ ELISpot experiments suggest that both melioidosis patients and HH contacts engage strong cross-immune IFN-γ responses between B. pseudomallei, B. thailandensis, and BTCV, despite low humoral responses in the HH cohort.…”
Section: Discussionmentioning
confidence: 99%
“…NanoRPLC-MS/MS was utilized in this study to identify proteins produced by B. pseudomallei while inside murine macrophages. The intracellular protein profile closely resembled the gene expression of B. pseudomallei in vivo, especially as described for human immune responses characterized using sera from patients infected with B. pseudomallei [25,26,[28][29][30][31][32][45][46][47][48]. We predicted that previously characterized Burkholderia proteins would be identified and serve as a positive control for our technical approach.…”
Section: Discussionmentioning
confidence: 74%
“…B. pseudomallei AhpC was found to be highly expressed in plasma from melioidosis survivors, but not in healthy controls [31]. In addition, T cell mediated immunity to AhpC was associated with protection against disease and shown to be a correlate of survival [46,48] and it represents a melioidosis vaccine candidate [30,46,48]. BPSL2748 is a putative AhpC-type peroxiredoxin, but it has not been as extensively studied as B. pseudomallei AhpC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Epitope identification is expensive and laborious, requiring experimental screening of large arrays of potential epitope candidates. However, recent works of epitope mapping of Burkholderia strains have been performed using the peptide microarray approach [ 59 , 60 , 61 ]. This technique relies on the use of libraries of synthesized linear peptides spotted on a single chip and screening for antigenicity using patients’ antisera.…”
Section: Bioinformatics Tools To Predict Immunogenic Epitopesmentioning
confidence: 99%